2017
DOI: 10.1038/s41598-017-17045-2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and transcriptomic analyses of drought stress responses of LY1306 tobacco strain

Abstract: This study aimed to investigate drought resistance of the LY1306 tobacco strain. Seedlings of tobacco strains LY1306, ZhongYan 100 (ZY100) and Hong Hua Da Jin Yuan (HHDJY) were treated with polyethylene glycol (PEG)-6000 to induce osmotic stress. As validation, water-deficit-induced drought treatments, including mild drought (MD; watering 1.5 L/week) and severe drought (SD, without watering) were carried out. Changes in cell morphology, leaf water potential, antioxidant enzyme activity, as well as contents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
(30 reference statements)
0
27
0
Order By: Relevance
“…For example, the transcription of CAT3 could be induced by drought and overexpression lines were insensitive to drought stress (Zou et al , 2015). In tobacco, biochemical and transcriptomic analyses showed that CAT transcript level and catalase enzyme activity were up‐regulated by drought stress treatment (Yang et al , 2017; Yin et al , 2015). The results we obtained are consistent with the view that NtCAT expression was induced by drought, and overexpression lines had high survival rates under drought stress conditions (Figure 1), suggesting that NtCAT acts as a positive regulator of drought tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the transcription of CAT3 could be induced by drought and overexpression lines were insensitive to drought stress (Zou et al , 2015). In tobacco, biochemical and transcriptomic analyses showed that CAT transcript level and catalase enzyme activity were up‐regulated by drought stress treatment (Yang et al , 2017; Yin et al , 2015). The results we obtained are consistent with the view that NtCAT expression was induced by drought, and overexpression lines had high survival rates under drought stress conditions (Figure 1), suggesting that NtCAT acts as a positive regulator of drought tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…PYL8 positively regulates ABA signaling during germination and abiotic stress responses. Furthermore, data showed that PYL8 plays essential roles in response to dark-induced senescence [102] and in drought stress [103]. An SNP variation was detected on a Cysteine protease response to dehydration (RD19A-like), which is a responsive gene to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…The T1 generations were said to be the transgenic tobacco lines that contained a single insertion, whose seeds were grown in the same conditions as described earlier. After three weeks, the seedlings were transferred to a hydroponic system and two weeks later, the seedlings of the transgenic tobacco were exposed to 100 mM NaCl [ 34 ], 15% PEG-6000 ( m / v ) [ 35 ] and 100 mM H 2 O 2 [ 36 ] in half strength Hoagland’s nutrient solution (24 h) for simulating salt, drought and oxidative stress, respectively. For cold stress, the seedlings were cultivated in half strength Hoagland’s solution at 4 °C [ 37 ].…”
Section: Methodsmentioning
confidence: 99%